Combined effect of Trichoderma harzianum and Vermicompost in the management of root knot nematode (Meloidogyne incognita) in tomato cv Pusa Ruby - ARYA, REKHA (Indian Phytopathology, 2016)
Root-knot nematode, Meloidogyne incognita is a potential pathogen threatening the cultivation of tomato. It causes significant yield losses per annum all over the world. For successful disease management of pathogen and sustainable tomato production, environmentally safe management practices are one of the most important approaches. Using a combination of eco-friendly practices seems an interesting idea. Keeping this in mind, a combination of Trichoderma harzianum and liquid Vermicompost was screened against M. incognita in tomato cv. Pusa Ruby. In present studies, the germination percentage of tomato cv Pusa Ruby was studied in soil infested with M. incognita and T. harzianum. Dosages were 3g/Kg and 5g/Kg soil for T. harzianum and 1000 J-2 larvae per kg soil for M. incognita. The soil was further amended with vermicompost at the rate of 100g/kg soil before the seeds were sown. All the three components were infested in soil separately and in different combinations. Germination percentage was calculated after 5, 10, 15 and 20 days. Results indicated that combined inoculations of T. harzianum and vermicompost proved effective in reducing infection of M. incognita and increasing germination percentage. The hatching and mortality of root knot nematode larvae were also observed in culture filtrate of T. harzianum and aqueous vermicompost separately. The percent reduction of larval emergence showed a significant positive correlation with increased concentration of culture filtrate and vermicompost. Although culture filtrate of T harzianum was more effective in reducing the hatching of larvae, there was a significant decrease shown by vermicompost as well in separate treatment. Most effective treatment was combination of both the inoculants.